An important superficial vein of the radial aspect of the forearm: An anatomical study - Madhubari Vathulya; Mohd Salahuddin Ansari (Indian Journal of Plastic Surgery)
Introduction: The superficial veins of upper limbs are seldom talked about. They are always avoided quoting them to be variable in anatomy. Other than the cephalic and basilic veins, no other superficial vein has caught the eyes of anatomists and other health professionals significantly. This article tries to explain the importance of a superficial vein that closely traces the radial vessels and explains its possible use in microvascular reconstruction. Materials and Methods: The forelimbs of 26 upper limbs of fresh frozen cadavers were dissected out. The anatomy of the superficial vein that follows the radial vessels was traced out from wrist to cubital fossa. Their relation to the deep venous system and cephalic veins was followed and documented. Results: All the 26 upper limbs showed the existence of the superficial vein that follows the radial vessels. The study also revealed the existence of venous perforators which are in turn the communication channels between the deep and superficial venous systems. Conclusion: The existence of the surface vein can logically hold an explanation for flap failure or success when one vein anastomosis is contemplated for radial forearm-free tissue transfers.